Sosialisasi Perguruan Tinggi Negeri (PTN) Universitas Pattimura Jalur SNBP, SNBT, Mandiri dan KIP Kuliah Universitas Pattimura kepada Siswa/Siswi SMA/SMK/MA Sederajad di Kabupaten Buru - Riry, Berty; Salakory, Melianus; Leuwol, Ferdinand Salomo (Jurnal Pengabdian Arumbai, 2024)
This community service activity aims to support the implementation of the Merdeka Belajar Curriculum in schools with limited access to technology through mentoring and the development of offline learning media. The program involves training and workshops for teachers to enhance their understanding of the Merdeka Belajar Curriculum and their ability to develop and use creative and effective offline learning media. The results of this activity show an increase in teachers' competence in implementing the curriculum, the development of various innovative offline learning media such as learning modules, educational posters, and simple teaching aids, as well as the preparation of lesson plans that are more adaptive to local conditions. Additionally, the engaging and interactive offline learning media successfully increased student participation and interest in learning. The evaluation of this activity indicates that mentoring and the development of offline learning media are strategic steps in improving the quality of education in areas with limited access to technology, thereby contributing to the equalization of educational quality throughout Indonesia.